Radio Free Asia (2019)
Das ist eine Talkshow zu den aktuellen politischen Themen, die das politische Schicksal der Uiguren betreffen und die Exiluiguren besonders interssieren. Hierbei finden sich unterschiedliche Videos zu dieser Sendung. - This is a talk show on current political issues that affect the political fate of the Uyghurs and are of particular interest to the exiles. There are different videos for this program.